(untitled) (World Bulletin of Management and Law, 2022)
The supply chain is one of the most important entrances to measuring the performance of organizations, as it includes all operational activities starting from the supply process through production operations to quick supplement and delivery to the customer. Performance measurement is the cornerstone for measuring the organization’s success in achieving its goals, as the effective supply chain contributes to enhancing the dimensions of organizations’ competition.